ANALYSIS OF IMPLEMENTATION STRATEGIES FOR THE ADOPTION OF E-LEARNING IN PUBLIC SECONDARY SCHOOLS: A CASE OF TRANS-NZOIA WEST SUB-COUNTY, KENYA - Wakasiaka, Mwichabe E.; Mungai, Prof. Chegge Peter; Lwangale, David Wafula; Wekesa, Jane (IJRDO - Journal of Applied Management Science, 2015)
This study focused on the topic Adoption of e-learning in public secondary schools; ananalysis of implementation strategies in Trans-Nzoia West Sub-County, Kenya. The studyoperated with the following objectives: to establish e-learning implementation strategies andto establish the extent of its implementation. Though the Kenya Institute of Education (KIE)developed e-learning Compact Discs (CDs) for eleven (11) subjects in Form 1 anddisseminated them to schools in the year 2005, many schools in the Sub-County do not usethem to supplement face to face teaching and the chalkboard prompting this study to analyzestrategies and extent and of their implementation. The study was guided by the theory ofPerceived Attributes (Rogers, 1995) which postulates the way potential adopters judge aninnovation. The study was carried out in Trans-Nzoia West Sub-County of Trans-NzoiaCounty in Kenya. Descriptive Survey research design was used to produce statisticalinformation about aspects of education that interest policy makers and educators (Borg andGall, 1989). The study targeted 58 secondary schools, 58 principals, 58 Board ofManagement (BoM) chairpersons, and Heads of Department (HoDs) of the 58 schools. Thesample size comprised of Seventeen (17) schools, Seventeen (17) BoM. members, Seventeen(17) principals and One hundred and four (104) HoDs making a total of 155. Instruments ofdata collection were questionnaire and interview schedules. Descriptive statistics usingpercentages and frequencies was used to analyze the collected data. The findings reflect theactual state of the adoption of e-learning in secondary schools. The findings revealed thatmost of the e-learning implementation strategies were lacking in secondary schools in TransNzoia West Sub-County. There was lack of trained teachers, basic structures and nofunctional computer labs in the area of ICT. The extent of implementation of e-learning insecondary schools in Trans-Nzoia West Sub-County would not be easily established. Thiswas because no school had indeed started adoption of e-learning.